Quality assessement in lntensive Care Medicine - Moreno, Rui (1997)
The techniques of quality assessement and quality improvement are not new in the business world. However, their application to medicine has been delayed and amateurish by the medical professionals and entities involved. The evaluation of our attitudes, procedures and results, when we aim at attaining better quality of care, has been until now imprecise, incidental and intuitive. It can and should be precise, systematic and rigorous. For that purpose, it is necessary to use a common language, which presupposes an in-depth knowledge ofthe various deflnitions pertaining to this matter. The authors present and discuss the more frequently used terminology, comment on the process of quality evaluation and quality improvement in medicine, when focusing on the targets and beneftts. Finally, the applicabillty of this global approach to intensive care medicine in the 90's is discussed.